PROBLEMATIKA PEMBELAJARAN HOME VISIT DI RAUDHATUL ATHFAL DARUL FALAH KARANGPLOSO MALANG - Bibi Winda Listyawati; Muhammad Hanif; Ika Anggraheni (Jurnal Dewantara, 2021)
This study aims to describe the Problems of Home Visit Learning at Raudlatul Atfal Darul Falah Karangploso Malang. This research uses a qualitative approach with the type of case study research which emphasizes more on explanations through words. The research subjects were early childhood children aged 5-6 years, classroom teachers, and parents. The data collection procedure was carried out by means of observation, interviews, and documentation. Data analysis techniques are carried out by reducing data, presenting data, and drawing conclusions. Each analysis is narrated descriptively and then concluded according to the research focus. Based on the data exposure and research findings, it was found that homevisit learning at Raudlatul Atfal Darul Falah Karangplso, was carried out on Monday-Saturday at 07.00 - 09.00. Learning activities are carried out semi-formally where all students do not wear school uniforms, the clothes used are free, neat and polite. Before the implementation of Home Visit learning begins, a teacher must prepare, including grouping students based on where they live. The group division is done with the aim of facilitating the learning process. The number of students in one class is fifteen children divided into three groups, where one group consists of 5 children. The problem faced by teachers, parents and students is the lack of cooperation and communication so that Home Visit Learning cannot be carried out properly. The involvement of parents in the success of the school program is needed for the smooth learning process. The form of cooperation carried out by a teacher is the teacher as the person who plans activities and assesses learning outcomes while parents as educators of children at home which aims to determine the learning process, this is done to determine the development of children during learning. Communicating with each other between parents and teachers is also very necessary because it is to know the development of students both when learning at school and learning at home.